ASSESSMENT OF MOTOR PERFORMANCE OF CHILDREN OF 6 TO 9 YEARS OLD - Abiko, Rafael Hideki (2013)
The aim of the study was to investigate the motor performance of children from Maringá-PR city. The sample consisted of 145 children (8.1 ± 1.0) years old of both sexes. The measurement instruments used were the Test of Gross Motor Development 2 (TGMD2), developed by Ulrich, validated by Valentini et al.The data acquisition was held in same school environment of children. Results have showed children demonstrated a motor performance considered “poor”, and girls showed better performance in general motor performance (p